Skozi vrata ven, skozi okno noter (out through the door, in through the window): Names of House Parts as Components of Slovenian and Slovak Phrasemes - Kmecová, Svetlana (Jezikoslovni zapiski, 2021)
The concepts of house and home, which are closely interconnected in language, are at the center of the linguistic picture of the world in every culture. They are outlined in the introduction of this article, and the subsequent sections deal with phraseological units in Slovenian and Slovak containing one of the chosen house parts as a component from a comparative point of view. The lexemes are mostly polysemous, and as parts of fixed expressions they bear both semantic and symbolic value. The fact that this semantic field is so numerous proves that the home is understood as one of the most important values in human life.